The brink of all we hate : English satires on women, 1660-1750 - Nussbaum, Felicity (University Press of Kentucky, 1984)
Examining the elements of the tradition of antifeminist satire in the Restoration and eighteenth century, and exploring its uses, Nussbaum reveals a clearer context in which many poems of the period will be read anew.